2010
DOI: 10.1093/ejo/cjq013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gingival display on smile aesthetics in Japanese

Abstract: The aim of this study was to evaluate the influence of the amount of gingival display on smile aesthetics as assessed by Japanese orthodontists and dental students. A coloured photograph of a smiling female, displaying the first molar to first molar, whose upper lip was tangent to the upper gingival margin of the upper central incisors (zero point), was constructed from different subjects. Gingival displays were modified by moving the teeth within the lip frame in 1 mm increments, from -5 to 5. Using a visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
77
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 21 publications
11
77
0
4
Order By: Relevance
“…This agrees with results of the studies by Ioi et al 9 6 , who claim that laywomen are less critical of smiles with greater gingival display than men, and with Cracel-Nogueira, Pinho 4 , who say that laywomen and dentists are more critical with respect to the degree of gingival display.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This agrees with results of the studies by Ioi et al 9 6 , who claim that laywomen are less critical of smiles with greater gingival display than men, and with Cracel-Nogueira, Pinho 4 , who say that laywomen and dentists are more critical with respect to the degree of gingival display.…”
Section: Discussionsupporting
confidence: 91%
“…Currently, many studies have shown that the characteristics of an aesthetic smile, according to dental professionals and laypersons, are different. Some of these studies have worked with computer modified photographs and are shown to be an effective method for evaluating the different perceptions 3,4,6,[9][10][11][12]14 . Analyzing the aesthetic perception of patients and professionals in relation to increased gingival display (gingival smile), it was observed that, according to general practitioner dentists and periodontists, 1.5 mm of gingival display compromises the aesthetics of the smile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 These differing results suggest that it is important to consider the ethnic and cultural background of both patients and evaluators when analyzing the smiles of orthodontic patients. Ioi et al 29 pointed out that there is insufficient evidence to support what is considered an attractive smile in the Japanese population. Therefore, the present study is the first to report about Height-1 and Height-4 among the 14 gingival display, 13 and maxillary gingival display, 18 was 0.53 6 0.90 mm in the nonmanipulated images of young female patients in group A.…”
Section: Discussionmentioning
confidence: 99%